2022
DOI: 10.1108/oir-10-2021-0547
|View full text |Cite
|
Sign up to set email alerts
|

Everyday life information seeking in South Korea during the COVID-19 pandemic: daily topics of information needs in social Q&A

Abstract: PurposeThis study investigated information needs on COVID-19 by identifying topics discussed on social questions and answers (Q&A) about daily routines, problems, and health issues for survival. A layered model of contexts for everyday life information seeking (ELIS) was adapted for interpreting topics to better understand the contexts in which users could relate information needs.Design/methodology/approachQuestions and answers posted on Naver Knowledge-iN were collected and analyzed during the first nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…This article's findings will also provide implications for health and risk management practice and health campaign development. Recent research on information needs reveals that questions and answers about symptoms and masks were dominant online during the pandemic (Kim and Oh, 2022). This study shows the internet has become an important channel for many people searching for COVID-19 information, which is consistent with previous studies (Hern andez-Garc ıa and Gim enez-J ulvez, 2020; Kim et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…This article's findings will also provide implications for health and risk management practice and health campaign development. Recent research on information needs reveals that questions and answers about symptoms and masks were dominant online during the pandemic (Kim and Oh, 2022). This study shows the internet has become an important channel for many people searching for COVID-19 information, which is consistent with previous studies (Hern andez-Garc ıa and Gim enez-J ulvez, 2020; Kim et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…Does that mean I am immunocompromised?”). In their analysis of COVID-19 information seeking on Naver Knowledge iN, Kim & Oh similarly identified topics related to the “cognitive context” (e.g., symptoms and masks) as well as the “situational context” (e.g., financial support, study, and work) [ 13 ]. Compared to their study, as well as other studies of general social media discourse [ 8 , 9 ], we found a higher prevalence of technical terms among the top words ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the sequential rise of topics within the ‘COVID-19 Vaccine’ theme–from ‘Development and Rollout,’ to ‘Safety and Side Effects,’ to ‘Dosage and Timing,’ to ‘Behavior Surrounding Vaccination’–mirrored the real-world progression of vaccine-related events. Kim & Oh similarly found that COVID-19 information needs related to the “social context” rose in prevalence later than information needs related to the “cognitive” and “situational” contexts [ 13 ]. Science communicators should thus be mindful of these temporal factors when fulfilling information needs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations